2023
DOI: 10.3390/ijerph20031836
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics Analysis of the Toxicological Impact of Enrofloxacin in an Aquatic Environment on the Chinese Mitten Crab (Eriocheir sinensis)

Abstract: Enrofloxacin is an important antimicrobial drug that is widely used in aquaculture. Enrofloxacin residues can have negative effects on aquatic environments and animals. The toxicological effects of different concentrations of enrofloxacin residues in cultured water on Chinese mitten crabs (Eriocheir sinensis) were compared. A histological analysis of the E. sinensis hepatopancreas demonstrated that the hepatopancreas was damaged by the different enrofloxacin residue concentrations. The hepatopancreas transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…In this study, 20 d of exposure to prometryn disrupted the structure of hepatic tubules and caused lumen swelling, which was similar to the results of our previous acute toxicity research [ 34 ], again proving the susceptibility of E. sinensis to exogenous herbicides. A similar pathology was observed in the hepatopancreas of E. sinensis after enrofloxacin exposure [ 63 ]. In addition, prometryn exposure significantly altered the structure of the intestinal morphology including shorter intestinal villi and thinner muscle layer, which is an important indicator of intestinal barrier function [ 64 ].…”
Section: Discussionsupporting
confidence: 63%
“…In this study, 20 d of exposure to prometryn disrupted the structure of hepatic tubules and caused lumen swelling, which was similar to the results of our previous acute toxicity research [ 34 ], again proving the susceptibility of E. sinensis to exogenous herbicides. A similar pathology was observed in the hepatopancreas of E. sinensis after enrofloxacin exposure [ 63 ]. In addition, prometryn exposure significantly altered the structure of the intestinal morphology including shorter intestinal villi and thinner muscle layer, which is an important indicator of intestinal barrier function [ 64 ].…”
Section: Discussionsupporting
confidence: 63%
“…Liu et al [ 199 ] observed that exposure to 0.4 mg/L NOR for 7 days resulted in significant damage to the testicular DNA of male C. auratus ; a parallel effect was noted in embryos of embryos of D. rerio [ 202 ]. Additionally, heightened concentrations of ENR induce a differential expression of genes related to the immune system and metabolism in the hepatopancreas of Eriocheir sinensis (genes for alkaline phosphatase, NF-kappa B inhibitor alpha, alpha-amylase, and beta-galactosidase-like) [ 203 ]. Furthermore, research has unveiled that FQs impact not only the replication and transcription of enzyme genes but also have the potential to induce the generation of drug-resistant bacteria and promote the production of resistant genes.…”
Section: Toxicity Of Fqsmentioning
confidence: 99%